2016
DOI: 10.1177/1535370216649061
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acoustic radiation force on osteoblasts in cell/hydrogel constructs for bone repair

Abstract: Ultrasound, or the application of acoustic energy, is a minimally invasive technique that has been used in diagnostic, surgical, imaging, and therapeutic applications. Low-intensity pulsed ultrasound (LIPUS) has been used to accelerate bone fracture repair and to heal non-union defects. While shown to be effective the precise mechanism behind its utility is still poorly understood. In this study, we considered the possibility that LIPUS may be providing a physical stimulus to cells within bony defects. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Toward this end, we have developed a methodology that can mechanically stimulate hydrogel-encapsulated cells using low-intensity pulsed ultrasound (LIPUS)-derived acoustic radiation force (ARF). 5 ARF is the force that is introduced when an area is irradiated with a sound field 6 and manifests itself by driving particles within the sound field to drift and cluster. Traditionally, ARF is used at very high intensities, as high as 1 MW/cm 2 , for techniques such as tissue imaging and elastography to evaluate the mechanical properties of intact human tissue, [7][8][9] but resulting thermal effects from the required high intensities limit its clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, we have developed a methodology that can mechanically stimulate hydrogel-encapsulated cells using low-intensity pulsed ultrasound (LIPUS)-derived acoustic radiation force (ARF). 5 ARF is the force that is introduced when an area is irradiated with a sound field 6 and manifests itself by driving particles within the sound field to drift and cluster. Traditionally, ARF is used at very high intensities, as high as 1 MW/cm 2 , for techniques such as tissue imaging and elastography to evaluate the mechanical properties of intact human tissue, [7][8][9] but resulting thermal effects from the required high intensities limit its clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…The pulse modulation of the LIPUS signal produces motion occurring at a frequency of 1 kHz, and has been shown to produce tissue movement in the nanometre range (Harrison et al, 2016); replication of this motion has been shown to generate the same phenotype in chondrocytes as stimulation with LIPUS (Argadine et al, 2005). More recently, Veronick et al (2016) showed that LIPUS stimulation induces movement of fluorescent beads encapsulated within a collagen hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports suggest that LIPUS does not affect cell proliferation . Akagi et al reported no influence of LIPUS on cell proliferation in rat bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…Akagi et al reported no influence of LIPUS on cell proliferation in rat bone marrow cells. Veronick et al demonstrated that LIPUS had no effect on MC3T3 mouse osteoblast cell proliferation on hydrogels. In our in vitro study, we also did not detect any effect of LIPUS on cell proliferation by CCK‐8 and PI assays.…”
Section: Discussionmentioning
confidence: 99%